Impact of bromide on halogen incorporation into organic moieties in chlorinated drinking water treatment and distribution systems. - Tan, J.; Allard, Sebastien; Gruchlik, Yolanta; McDonald, S.; Joll, Cynthia; Heitz, Anna (2016)
The impact of elevated bromide concentrations (399 to 750µg/L) on the formation of halogenated disinfection by-products (DBPs), namely trihalomethanes, haloacetic acids, haloacetonitriles, and adsorbable organic halogen (AOX), in two drinking water systems was investigated. Bromine was the main halogen incorporated into all of the DBP classes and into organic carbon, even though chlorine was present in large excess to maintain a disinfectant residual. Due to the higher reactivity of bromine compared to chlorine, brominated DBPs were rapidly formed, followed by a slower increase in chlorinated DBPs. Higher bromine substitution and incorporation factors for individual DBP classes were observed for the chlorinated water from the groundwater source (lower concentration of dissolved organic carbon (DOC)), which contained a higher concentration of bromide, than for the surface water source (higher DOC). The molar distribution of adsorbable organic bromine to chlorine (AOBr/AOCl) for AOX in the groundwater distribution system was 1.5:1 and almost 1:1 for the surface water system. The measured (regulated) DBPs only accounted for 16 to 33% of the total organic halogen, demonstrating that AOX measurements are essential to provide a full understanding of the formation of halogenated DBPs in drinking waters. In addition, the study demonstrated that a significant proportion (up to 94%) of the bromide in source waters can be converted AOBr. An evaluation of AOBr and AOCl through a second groundwater treatment plant that uses conventional treatment processes for DOC removal produced 70% of AOX as AOBr, with 69% of the initial source water bromide converted to AOBr. Exposure to organobromine compounds is suspected to result in greater adverse health consequences than their chlorinated analogues. Therefore, this study highlights the need for improved methods to selectively reduce the bromide content in source waters.